2017
DOI: 10.1007/s10461-017-1765-y
|View full text |Cite
|
Sign up to set email alerts
|

The Technology Acceptance Model for Resource-Limited Settings (TAM-RLS): A Novel Framework for Mobile Health Interventions Targeted to Low-Literacy End-Users in Resource-Limited Settings

Abstract: Background Although mobile health (mHealth) technologies have shown promise in improving clinical care in resource-limited settings (RLS), they are infrequently brought to scale. One limitation to the success of many mHealth interventions is inattention to end-user acceptability, which is an important predictor of technology adoption. Methods We conducted in-depth interviews with 43 people living with HIV in rural Uganda who had participated in a clinical trial of a short messaging system (SMS)-based interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 52 publications
5
82
0
Order By: Relevance
“…Perceived usefulness measures the performance of specific technology in prompting people to act, whereas perceived ease of use indicates the degree of difficulty in using specific technology. Scholars have subsequently verified the effectiveness of this model [59], and the influence of perceived usefulness and perceived ease of use on the adoption of mobile health care have been demonstrated in numerous studies [60][61][62]. Therefore, the technological dimension of this study involves usefulness and ease of use.…”
Section: Technological Dimension (D 1 )mentioning
confidence: 76%
“…Perceived usefulness measures the performance of specific technology in prompting people to act, whereas perceived ease of use indicates the degree of difficulty in using specific technology. Scholars have subsequently verified the effectiveness of this model [59], and the influence of perceived usefulness and perceived ease of use on the adoption of mobile health care have been demonstrated in numerous studies [60][61][62]. Therefore, the technological dimension of this study involves usefulness and ease of use.…”
Section: Technological Dimension (D 1 )mentioning
confidence: 76%
“…Still other authors noted this dichotomy within their reported results with some participants expressing significant privacy concerns and others stating it to not be an issue [146,147]. While some users expressed such concerns related to collection of highly sensitive-data, such as that related to behavioral health, reproductive health, or HIV status [135,[148][149][150][151], other users who provided such data still reported little unease related to their privacy [139,142,[152][153][154]].…”
Section: Dynamic User Attitudes Toward Privacymentioning
confidence: 98%
“…Those in the intervention arm will receive additional questions related to the enhanced app features. The outcomes selected for analysis correspond with the Technology Acceptance Model for Resource-Limited Settings (TAM-RLS) framework, which was designed to draw attention to end-user acceptability as a predictor of mHealth technology adoption in lowresource settings [48].…”
Section: Secondary Outcome 2: Acceptability and Feasibility Of Carecomentioning
confidence: 99%